Unit operations of chemical engineering. warren L. mccabe, julian C. smith, peter harriott - McCabe, Warren L. ([S.l.] : McGraw-Hill Higher Education, 2005)
Unit Operations of Chemical Engineering, 7th edition continues its lengthy, successful tradition of being one of McGraw-Hill's oldest texts in the Chemical Engineering Series. Since 1956, this text has been the most comprehensive of the introductory, undergraduate, chemical engineering titles available. Separate chapters are devoted to each of the principle unit operations, grouped into four sections: fluid mechanics, heat transfer, mass transfer and equilibrium stages, and operations involving particulate solids. Now in its seventh edition, the text still contains its balanced treatment of theory and engineering practice, with many practical, illustrative examples included. Almost 30 per cent of the problems have been revised or are new, some of which cover modern topics such as food processing and biotechnology. Other unique topics of this text include diafiltration, adsorption and membrane operations.
International Edition.
Keywords: chemical engineering